2018
DOI: 10.1016/j.neurobiolaging.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical effects of mutant ubiquitin on Aβ plaque formation in an Alzheimer mouse model

Abstract: Amyloid-β (Aβ) plaques are a prominent pathological hallmark of Alzheimer's disease (AD). They consist of aggregated Aβ peptides, which are generated through sequential proteolytic processing of the transmembrane protein amyloid precursor protein (APP) and several Aβ-associated factors. Efficient clearance of Aβ from the brain is thought to be important to prevent the development and progression of AD. The ubiquitin-proteasome system (UPS) is one of the major pathways for protein breakdown in cells and it has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 74 publications
0
13
1
Order By: Relevance
“…Reduction of proteasomal chymotrypsin-like activities was observed in the brain including hippocampus of AD animal models [9]. It is believed that the UPS can degrade APP proteins in the brain [10], and reduce the accumulation of extracellular amyloid proteins by regulating the production and the degradation of Aβ [11,12]. Biochemical and morphological examinations of the brain of AD patients showed that phosphorylated Tau oligomer proteins accumulated on both sides of the synapse where ubiquitinated proteins, proteasome components and related chaperone proteins were also enriched, implicating that synaptic Tau protein aberrant aggregation may be an important mediator of proteotoxicity responsible for synaptic malfunction in AD [13].…”
mentioning
confidence: 99%
“…Reduction of proteasomal chymotrypsin-like activities was observed in the brain including hippocampus of AD animal models [9]. It is believed that the UPS can degrade APP proteins in the brain [10], and reduce the accumulation of extracellular amyloid proteins by regulating the production and the degradation of Aβ [11,12]. Biochemical and morphological examinations of the brain of AD patients showed that phosphorylated Tau oligomer proteins accumulated on both sides of the synapse where ubiquitinated proteins, proteasome components and related chaperone proteins were also enriched, implicating that synaptic Tau protein aberrant aggregation may be an important mediator of proteotoxicity responsible for synaptic malfunction in AD [13].…”
mentioning
confidence: 99%
“…To investigate the effects of UBB +1 expression on APP processing, we carried out secretase activity measurements on brain tissue samples from different mouse lines [ 5 ]. In APPPS1 mice, a partial decrease in γ-secretase activity was found compared to wild-type mice, in agreement with disruption of normal γ-secretase function by the PS1-ΔE9 mutation present in these animals (presenilin is the catalytic component of the γ-secretase complex).…”
mentioning
confidence: 99%
“…Therefore, changes in γ-secretase activity indicated altered carboxypeptidase-like cleavage in this assay. How UBB +1 exerts this stimulating effect on γ-secretase is not clear, but a potential mechanism may involve regulation of presenilin expression [ 5 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations